Immune Responses of Wistar Rat (Rattus novergicus) on Adduction of Humid Acid from Borneo Peat Soil - Diah Wulandari Rousdy; Rahmawati Rahmawati; Rikhsan Kurniatuhadi (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2016)
Peat soil is a type of soil that dominates the island of Borneo. Typical compounds in peat soil is humic acid. Various in vitro studies performed have shown peat subtropical humic compounds can stimulate the immune system. However, in vivo study on animal has not been done. This study aimed to determine the effect of humic acid extracted from peat soil of Borneo against the immune system, both of non-specific and specific immunity Wistar rats (Rattus novergicus). Research using a completely randomized design with five treatments and five replicates, the normal controls, a positive control (isoprinosine), humic acid 125; 250; 500 mg/kg. Humic acid was administered orally for 10 days. The results showed humic acid adduction did not significantly affect levels of hemoglobin, erythrocytes and hematocrit. Humic acid adduction of 125 mg/kg significantly affects the total leukocyte count and differential leukocyte. Humic acid 125 mg/kg also showed increased phagocytic index better than normal controls. All humic acid treatments do not provide a significant effect on the total amount of antibody. The results of this study can be used for the development of Borneo tropical peat resources as natural imunostimulant.How to CiteRousdy, D. W., Rahmawati, R. Kurniatuhadi, R. (2016). Immune Responses of Wistar Rat (Rattus novergicus) on Adduction of Humid Acid from Borneo Peat Soil. Biosaintifika: Journal of Biology Biology Education, 8(3), 401-406.